Highly diastereo- and enantioselective synthesis of spirooxindole-cyclohexaneamides through N, N′-dioxide/Ni(ii)-catalyzed Diels–Alder reactions. Issue 12 (30th January 2017) - Zhou, Yuhang; Lu, Yan; Hu, Xinyue; Mei, Hongjiang; Lin, Lili; Liu, Xiaohua; Feng, Xiaoming
Abstract : New kinds of spirooxindole-cyclohexaneamides were achieved in up to 99% yield, >95 : 5 dr, and 99% ee via N, N ′-dioxide/Ni(ii )-catalyzed Diels–Alder reactions. Abstract : Highly efficient asymmetric Diels–Alder reactions of methyleneindolinones with 1, 3-dienylcarbamates and 1, 2-dihydropyridines have been accomplished by using a chiral N, N ′-dioxide/nickel(ii ) complex as an efficient catalyst. New kinds of spirooxindole-cyclohexaneamides were achieved in up to 99% yield, >95 : 5 dr, and 99% ee.